Three-Component Synthesis of Some New Coumarin Derivatives as Anticancer Agents - Alshabanah, Latifah A.; Al-Mutabagani, Laila A.; Gomha, Sobhi M.; Ahmed, Hoda A. (Frontiers in Chemistry, 2022)
A three-component reaction for the synthesis of novel 3-heteroaryl-coumarin utilizing acetylcoumarin synthon, under ultrasonic irradiation was developed using chitosan-grafted-poly(vinylpyridine) as an ecofriendly catalyst. The process is a simple, facile, efficient procedure for the preparation of compounds displaying a thiazole ring linked to coumarin moiety. Moreover, all the products were evaluated for their anticancer activity against HEPG2-1. The results revealed that three new compounds showed promising anticancer activity